Fiscal Spending and Economic Growth: Some Stylized Facts - Céline Carrère; Jaime de Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
Using an "event analysis", this paper complements the cross-country approach to the study of fiscal correlates of growth. Data on fiscal expenditures and growth for a database of 140 countries (118 developing countries) over 1972-2005 are reorganized around turning points providing a summary but encompassing description of "what is in the data". For this sample, the probability of occurrence of a fiscal event is about 10%, and, the probability of a growth event once a fiscal event had occurred is around 26 %. For developing countries, fiscal events followed by growth events occur under situations of (i) significantly lesser deficit, (ii) fewer resources devoted to non-interest General Public Services and (iii) shift in primary expenditures towards Transport & Communication.
Keywords: E62; H62; O11; O23; 330